Diagnóstico energético e propostas de melhorias em uma panificadora no município de Abaetetuba-PA - SANTOS JUNIOR, Admildo Azevedo (2019)
This research proposes an energy diagnosis and an elaboration of improvement proposals, aiming electricity consumption reduction in a bakery, located in Abaetetuba city, state of Pará. The owner and collaborators were interviewed in order to obtain data on electricity consumption and characteristics of the building. Subsequently, two proposals were made aiming improvements, taking into account the main concepts of energy efficiency. The first proposal was based in the analysis of Pareto, which admits a scenario where a lower cost of investment exists, being suggested an exchange of just the equipment which has greater influence in the consumption of electricity; and the second proposed the exchange of old and / or inefficient equipment. After the proposals were obtained, economical analysis methods (simple payback, discounted payback, net present value) were used to verify financial viability. Finally, it was shown that the two proposals had valid results, giving the owner an autonomy in the decision of which way will be used, since the main differences between them were cost and the return of the investment in a short period of time.